Apple Maggot, Apple Maggot Fly, Rhagoletis pomonella (Walsh) (Insecta: Diptera: Tephritidae) - Howard V. Weems, Jr.; Thomas R. Fasulo (EDIS)
The apple maggot, Rhagoletis pomonella (Walsh) (also known as the "railroad worm") is an insect native to North America. Originally it fed in the fruit of wild hawthorn (Crataegus spp.), but during the past 130 years it has become a primary pest of cultivated apples, especially in the northeastern United States and southeastern Canada. Summer- and early fall-maturing varieties are particularly vulnerable, but hard winter apples are sometimes infested. Thin skinned sweet and subacid varieties are most susceptible, but acid varieties may be attacked. Plum, pear, and cherries also serve as hosts, but usually the apple maggot is not a serious pest of these fruits. Crab apples are invariably infested by this pest. A closely related species, the blueberry maggot fly (Rhagoletis mendax Curran), is important as a pest of cultivated blueberries. This document is EENY-261 (originally published as DPI Entomology Circular 126), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: January 2002.